HEALTH RELATED QUALITY OF LIFE OF STUDENTS WITH PHYSICAL AND SENSORY IMPAIRMENTS IN SPECIAL AND INTEGRATED SCHOOLS IN IBADAN. (2012)
The determination of Health-Related Quality of Life (HR-QoL) is useful for assessing the impact of health and illness on people’s physical, psychological and social functioning. In Nigeria, the HR-QoL of students (who are mostly adolescents) with physical and sensory impairments has not been adequately researched. There is need for scientific basis for comparative description of the experiences of Students with physical and sensory impairments (SwPSI) in special schools (SS) and integrated schools (IS). Further, the self-perceived needs of these students are yet to be assessed as well as factors influencing their HR-QoL An interviewer-administered questionnaire adapted from the World Health Organization International Classification of Functioning, Disease and Health and Short-Form Health Survey-36, was used to obtain information from all 330 eligible students in 7 IS and 8 SS in Ibadan. Students less than 10 years old and those who had mental disabilities in combination with physical disabilities were excluded. Cluster sampling method was used. Respondents’ HR-QoL was assessed using 84-point scale. Scores of < 41and > 42 points were taken as low and high HR-QoL respectively. Domains of HR-QoL assessed with points include interpersonal relationship-11, general participation-15, performance in physical activities-19, general health-12, vitality-12 and mental health-15. Data were analyzed using descriptive statistics and t test. Participants’ mean age was 15+3.9 years and 57.6% were males. Respondents from SS and IS constituted 59.7% and 40.3% respectively. The respondents included those with hearing and speech impairments (32.1%), hearing impairments only (24.2%), multiple physical deformities= (12.4%), speech impairments only (7.0%), visual impairments only (4.5%), limb impairments (13.6%), hearing impairments with other physical deformities (2.7%), speech impairments with other physical deformities (2.7%) and other types of physical deformities (0.6%). The mean HR- QoL scores of respondents in SS and IS were 48.3+10.6 and 50.1+10.0 respectively (p>0.05). The respective domain HR-QoL scores of students in IS and SS were: interpersonal relationship-(IS-7.5, SS-7.1) general participation-(IS-9.0, SS-7.7) performance in physical activities-(IS-12.1, SS-12.0) general health-(IS-7.4, SS-7.3) vitality-(IS-6.3, SS-6.1) and mental health-(IS-7.7, SS-8.2). Students in IS had higher scores in all domains except mental health. Students with visual impairment had the highest (52.1) HR-QoL score while those with multiple physical impairments had the least (39.5; p<0.05). Students in IS with visual impairment had highest scores in general health (9.9) and interpersonal relationship (8.8) while students in SS with hearing impairments had highest scores in general participation (8.3), vitality (7.1), general health (8.2) and mental health (9.2; p<0.05). The various needs identified by students in IS included more of Physiological needs and self-actualization needs while those in SS identified more of need for love and belonging and self-esteem needs. Factors identified in this study to be significantly associated with HR-QoL of SwPSI include family environment, school environment, type of impairment, use of individual education plan (IEP) and parental socio-economic status. Students kept in special schools had lower quality of life. It is therefore more beneficial to enroll students with limb, visual and speech impairments in integrated schools in order to improve their HR-QoL.